Avenues of understanding: mapping the intersecting barriers to adaptation in Namibia. (15th March 2020) - Davies, Julia Elaine; Spear, Dian; Ziervogel, Gina; Hegga, Salma; Ndapewa Angula, Margaret; Kunamwene, Irene; Togarepi, Cecil
ABSTRACT: The existing literature on barriers to adaptation focuses predominantly on the broad, generic factors, such as financial, technological or institutional factors, as examples that might constrain adaptation. Not enough is known, however, about how barriers converge in localities, what drives them and how they interact to affect adaptation processes and outcomes. This paper considers the barriers to adaptation in Namibia through the lens of the 'adaptation activity space' – a framework that positions the adapting system in relation to its environment. In doing so, it questions not only what types of barriers are encountered, but what their underlying drivers are and how the relationships among them influence adaptation on the ground. Two intersecting 'avenues' within Namibia's adaptation activity space are explored, namely: (1) the policy-practice partition and (2) the adaptive capacity challenge. Each of these avenues tells a story about the complex nature of barriers and points to the need for greater integration between government spheres, across temporal scales and among actor groups. Such integration is necessary for addressing the barriers to adaptation and for paving the way to a more effective and sustainable adaptation activity space in Namibia.